Trecking the historical concerns for effi ciency and eff ectiveness in the study and practice of Public Administration - BC, Basheka; Dominique, Uwizeyimana (African Journal of Governance and Public Leadership (AJoGPL), 2021)
is paper attempts to re-introduce the ideologies through historicizing the debates and then make a case for their relevance in today’s public administration systems. Public administration in its dual nature of being rst; a discipline of academic study and second; a eld of practice has indeed trekked a long journey and has had its primary concern being that of how to ensure governments work better in the managing public a airs. Undeniably, the need to promote administrative e ciency and e ectiveness has occupied the minds of classical and contemporary scholars and practitioners in almost an equal measure. e concerns of administrative e ciency and e ectiveness are debates which are as old as the discipline of public administration itself but also the concerns of the long journey of the practices of public administration have trekked the journey of civilization. While public administration and Governance scholars agree on the need for building administrative systems which are e cient and e ective, there remains divergence views on how the two can be promoted. ere are therefore a range of ideologies and benchmarks that have been propounded that once followed could promote e ciency and e ectiveness of government.